2020
DOI: 10.3389/fimmu.2020.573662
|View full text |Cite
|
Sign up to set email alerts
|

Immunesenescence: A Predisposing Risk Factor for the Development of COVID-19?

Abstract: Bearing a strong resemblance to the phenotypic and functional remodeling of the immune system that occurs during aging (termed immunesenescence), the immune response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent of Coronavirus disease 2019 (COVID-19), is characterized by an expansion of inflammatory monocytes, functional exhaustion of lymphocytes, dysregulated myeloid responses and the presence of highly activated senescent T cells. Alongside advanced age, male gender and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 293 publications
1
49
0
Order By: Relevance
“…Immunosenescence and inflammaging are high risk factors for severe COVID-19 in the elderly [ 1 , 2 , 17 , 18 ]. As age-related thymic involution contributes to immunosenescence and inflammaging ( Figure 1 A, Table 1 third column) [ 16 ], thymic function should also be considered as a potential player in aged populations versus young [ 19 , 20 ], and may also impact vaccination efficiency in the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…Immunosenescence and inflammaging are high risk factors for severe COVID-19 in the elderly [ 1 , 2 , 17 , 18 ]. As age-related thymic involution contributes to immunosenescence and inflammaging ( Figure 1 A, Table 1 third column) [ 16 ], thymic function should also be considered as a potential player in aged populations versus young [ 19 , 20 ], and may also impact vaccination efficiency in the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…Another prominent feature of COVID-19 severity is the association with advanced age [ 1 , 2 , 66 , 67 ]. Below the role of comorbidities, which tend to become more frequent during the aging process, a potential contributor to COVID-19 severity in older people may be represented by the subtle chronic inflammatory status called inflammaging (one of the three hallmarks of immunosenescence—an increase in serum cytokines impairing the effectivity of immune responses) and by the age-related progressive reduction in the ability to trigger effective antibody and cellular responses against infections and vaccinations [ 66 , 68 , 69 , 70 , 71 ]. Thus, immunosenescence represents a further potential contributor to the insurgence of fatal complications in COVID-19 [ 8 , 62 , 63 ].…”
Section: Other Immune Response Genesmentioning
confidence: 99%
“…Thus, immunosenescence represents a further potential contributor to the insurgence of fatal complications in COVID-19 [ 8 , 62 , 63 ]. Lymphopenia and accumulation of immune cells showing immunophenotypic and functional signs of exhaustion were commonly documented in COVID-19 patients, correlating with age and severity [ 43 , 68 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ]. This strong resemblance to immunosenescence makes COVID-19 a possible scenario to deepen the knowledge about the molecular basis affecting normal immune cell metabolism/lifespan/turnover and to determine the importance of genetic variants and epigenetic modifications behind the appearance of inflammaging and immunosenescence [ 66 , 85 , 86 , 87 , 88 ].…”
Section: Other Immune Response Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the other differences, we focus on the observation that the infection is significantly more lethal in elderly people [17,18,19,20]. Some studies have focused on the possible link between increased mortality rate and some characteristics of elderly people [21,22]. These studies suggested the potential effect of the virus as a trigger activating the decompensation of other chronic conditions [23,24,25,26].…”
Section: Introductionmentioning
confidence: 99%